Evaluation of Brix refractometer as an on-farm tool for colostrum IgG evaluation in Italian beef and dairy cattle. Issue 2 (6th May 2021) - Pisello, Lorenzo; Forte, Claudio; D'Avino, Nicoletta; Pisano, Rocco; Hyatt, Doreene Rose; Rueca, Fabrizio; Passamonti, Fabrizio
Abstract: In this study it is hypothesized that there are differences between immunoglobulin G (IgG) content in colostrum from beef (Chianina, Podolica) and dairy (Holstein Friesian) cows and that variables such as breed, and parity can influence IgG content. The further objective was to determine if these factors may vary in terms of sensitivity, specificity and the cut point when data obtained with the digital Brix refractometer is compared with the gold standard radial immunodiffusion assay (RID). A total of 90 samples of first-milking colostrum were collected within 2 h after parturition. IgG concentration was determined indirectly by digital Brix refractometer and directly by RID. Results obtained by RID were compared among breed and parity. For the digital Brix refractometer, sensitivity and specificity to detect colostrum with an IgG concentration lower than 50 g/l were calculated and the optimal cut-point was selected for each breed. Samples containing less than <50 g/l IgG accounted for 15.9% of the total. Parity influenced colostral IgG concentration and beef cows had a higher mean concentration of IgG (101.1 g/l in Chianina and 90.6 g/l in Podolica) than dairy cows (71.1 g/l in Holstein Friesian) First parity Chianina cows had the highest IgG mean content (116.1 g/l). At the optimal cut-point for Brix refractometer (20%) sensitivity and specificity were 0.93 (0.84–0.97) and 0.81 (0.70–0.88), however, a breed-related cut-point could be used to reduce evaluation error. Linear regression modeling showed that refractometer data were related to RID ( r = 0.78). Results obtained suggest that breed and parity can influence IgG content of colostrum and, despite the Brix refractometer being an excellent on-farm tool, a breed-based definition of optimal cut point is needed.